If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -5)(x + 3) = 8 Reorder the terms: (-5 + 2x)(x + 3) = 8 Reorder the terms: (-5 + 2x)(3 + x) = 8 Multiply (-5 + 2x) * (3 + x) (-5(3 + x) + 2x * (3 + x)) = 8 ((3 * -5 + x * -5) + 2x * (3 + x)) = 8 ((-15 + -5x) + 2x * (3 + x)) = 8 (-15 + -5x + (3 * 2x + x * 2x)) = 8 (-15 + -5x + (6x + 2x2)) = 8 Combine like terms: -5x + 6x = 1x (-15 + 1x + 2x2) = 8 Solving -15 + 1x + 2x2 = 8 Solving for variable 'x'. Reorder the terms: -15 + -8 + 1x + 2x2 = 8 + -8 Combine like terms: -15 + -8 = -23 -23 + 1x + 2x2 = 8 + -8 Combine like terms: 8 + -8 = 0 -23 + 1x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -11.5 + 0.5x + x2 = 0 Move the constant term to the right: Add '11.5' to each side of the equation. -11.5 + 0.5x + 11.5 + x2 = 0 + 11.5 Reorder the terms: -11.5 + 11.5 + 0.5x + x2 = 0 + 11.5 Combine like terms: -11.5 + 11.5 = 0.0 0.0 + 0.5x + x2 = 0 + 11.5 0.5x + x2 = 0 + 11.5 Combine like terms: 0 + 11.5 = 11.5 0.5x + x2 = 11.5 The x term is 0.5x. Take half its coefficient (0.25). Square it (0.0625) and add it to both sides. Add '0.0625' to each side of the equation. 0.5x + 0.0625 + x2 = 11.5 + 0.0625 Reorder the terms: 0.0625 + 0.5x + x2 = 11.5 + 0.0625 Combine like terms: 11.5 + 0.0625 = 11.5625 0.0625 + 0.5x + x2 = 11.5625 Factor a perfect square on the left side: (x + 0.25)(x + 0.25) = 11.5625 Calculate the square root of the right side: 3.400367627 Break this problem into two subproblems by setting (x + 0.25) equal to 3.400367627 and -3.400367627.Subproblem 1
x + 0.25 = 3.400367627 Simplifying x + 0.25 = 3.400367627 Reorder the terms: 0.25 + x = 3.400367627 Solving 0.25 + x = 3.400367627 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.25' to each side of the equation. 0.25 + -0.25 + x = 3.400367627 + -0.25 Combine like terms: 0.25 + -0.25 = 0.00 0.00 + x = 3.400367627 + -0.25 x = 3.400367627 + -0.25 Combine like terms: 3.400367627 + -0.25 = 3.150367627 x = 3.150367627 Simplifying x = 3.150367627Subproblem 2
x + 0.25 = -3.400367627 Simplifying x + 0.25 = -3.400367627 Reorder the terms: 0.25 + x = -3.400367627 Solving 0.25 + x = -3.400367627 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.25' to each side of the equation. 0.25 + -0.25 + x = -3.400367627 + -0.25 Combine like terms: 0.25 + -0.25 = 0.00 0.00 + x = -3.400367627 + -0.25 x = -3.400367627 + -0.25 Combine like terms: -3.400367627 + -0.25 = -3.650367627 x = -3.650367627 Simplifying x = -3.650367627Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.150367627, -3.650367627}
| 4x^2-16x=-3 | | 8=n+14 | | 5x^2+8x=2 | | 4x^2-9x=3 | | sin(8*x)=0.15 | | 3y/10-2=y/5+3 | | x^2+4-x(2x-1)=0 | | P=nr+2r+2a | | (20x^2)/(48,000-10x^2) | | 4p-8q=3p+2 | | 3(2x+5)+9=4x-38 | | 4x+3+7x=33 | | x^3-x^2-x=2015 | | 3r+6/6=3r-12/3 | | 3r+20=35 | | 12x-134=3x-8 | | log(5x)-log(5)=2.35 | | 94-7x=11x+20 | | 4x+1+2x-19=180 | | 3y-7=12y+65 | | (.9t^2)+(8t)-50=0 | | x^3+x^2-19x+39=0 | | 8-10x=26-24x | | 10x-8=7x-5 | | 3+8y=4y-5 | | 11-ln(4-x)=0 | | 4-4/3 | | (-2/3)(-2) | | 110-4x=23x+23 | | (16k+8k+2)+(-8k+3)=0 | | y^2+y=2.5 | | 2f-9=2f+1 |